2022
DOI: 10.1177/23969873221129080
|View full text |Cite
|
Sign up to set email alerts
|

Regular medication as a risk factor for intracranial aneurysms: A comparative case–control study

Abstract: Background: Previous medical history strongly contributes to the genesis of intracranial aneurysms (IA). A possible impact of regular medication on the occurrence of abdominal aortic aneurysms has been reported. Aim: To evaluate the value of regular medication on the risk of development and rupture of IA. Methods: Data on medication use and related comorbidities were obtained from the institutional IA registry. A 1:1 age- and sex-matched patient sample was collected from the population-based Heinz Nixdorf Reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…4 One cross-sectional study even found CCBs were independently associated with the presence of IAs. 5 Mendelian Randomization (MR) analysis is a complementary approach for assessing the causal effects of risk factors in observational studies using genetic variation. It uses genetic variants (single-nucleotide polymorphisms (SNPs)) as proxies for exposure to certain risk factors to investigate their effects on an outcome of interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 One cross-sectional study even found CCBs were independently associated with the presence of IAs. 5 Mendelian Randomization (MR) analysis is a complementary approach for assessing the causal effects of risk factors in observational studies using genetic variation. It uses genetic variants (single-nucleotide polymorphisms (SNPs)) as proxies for exposure to certain risk factors to investigate their effects on an outcome of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Such drug-target mendelian randomization can mimic pharmacological clinical trials and has been used previously to anticipate clinical benefits and adverse effects of therapeutic interventions. 5 Herein, we performed a two-sample MR analysis to investigate the causal effects of genetically determined BP and genetic proxies for antihypertensive drug classes on the risk of IA and SAH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 One crosssectional study even found CCBs were independently associated with the presence of IAs. 6 Mendelian Randomization(MR) analysis is a complementary approach for assessing the causal effects of risk factors in observational studies using genetic variation. 7 It uses genetic variants (single-nucleotide polymorphisms [SNPs]) as proxies for exposure to certain risk factors to investigate their effects on an outcome of interest.…”
Section: Introductionmentioning
confidence: 99%
“…5 One cross-sectional study even found CCBs were independently associated with the presence of IAs. 6…”
Section: Introductionmentioning
confidence: 99%